On the Role of Gesinnung in Kant’s Ethics and Philosophy of Religion. Part II - Alexei N. Krouglov (Кантовский сборник, 2019)
The sources of Kant’s term Gesinnung and a review of the problems of its translation into English were presented in the first part of this article; the second part examines the novel features that Kant brings to the interpretation of this concept in the critical period. In the Critique of Practical Reason these include the questions of manifestation of Gesinnung in the world, apprehended through the senses, the method of establishing and the culture of truly moral Gesinnung, as well as the problem of the immutability of Gesinnung in the progress towards the good. The new theses that appear in Religion within the Bounds of Bare Reason are Gesinnung as the internal subjective principle of maxims, on virtue as evidence of the presence of Gesinnung, on act as a manifestation of Gesinnung, on the unintelligibility of Gesinnung in its noumenal, suprasensible character, on the innateness of Gesinnung in the sense that it exists not in time, but in the form of its acceptance by free expression of the will, on the singleness of Gesinnung and its indivisibility into periods, on revolution in Gesinnung as distinct from empirical reform, on the creation of the new human being as distinct from the ancient one as a result of the revolution of Gesinnung, on the link between the revolution in Gesinnung and “conversion” or second birth. After discussing the problem of distinguishing the terms Gesinnung and Denkungsart in translation as well as a review of all the existing variants of translating Kant’s concept of Gesinnung into Russian (aspiration, inclination, intention, virtue, virtuousness, conviction, attitude, mode of thinking, thoughts, mood, disposition and umonastroenie), the author comes to the conclusion that the uniform variant umonastroenie is best suited for Russian translations of Kant’s works.